INTEGRATED TRI-DOMAIN MODEL (SOCIAL–LEGAL–HEALTH) FOR BUILDING COMMUNITY RESILIENCE IN THE ERA OF GLOBAL HEALTH CRISES - Santoso, Aris Prio Agus; Rezi, Rezi; Soares, Domingos; Astuti, Oktavia Ayu Sekar (LPPM Universitas Duta Bangsa Surakarta, 2025)
The absence of a model that simultaneously integrates the social, legal, and health dimensions hinders efforts to build community resilience in the era of global health crises. This study develops the Integrative Tridomain Model (Social–Legal–Health) to design comprehensive interventions that sustainably strengthen community resilience amid global health crises. Employing a conceptual approach with a descriptive orientation, this research constructs the Integrative Tridomain Model through a systematic synthesis of cross-disciplinary literature to broaden the understanding of community resilience in the context of global health emergencies. The findings indicate that the development of the Integrative Tridomain Model marks a paradigmatic leap in conceptualizing and fostering community resilience during global health crises. The model offers an epistemological synthesis that unites social, legal, and health knowledge; an ontological framework that perceives resilience as a systemic and relational entity; and an axiological foundation that prioritizes humanitarian values, justice, and sustainability as its core objectives. By merging the strengths of these three domains, the model not only addresses existing challenges but also shapes a more adaptive and inclusive order, enabling communities to endure and thrive in the face of complex and recurrent uncertainties.